2009
DOI: 10.1158/1940-6207.capr-09-0121
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Randomized, Placebo-Controlled Trial of Green Tea Extract in Patients with High-Risk Oral Premalignant Lesions

Abstract: Epidemiologic and preclinical data support the oral-cancer prevention potential of green tea extract (GTE). We randomly assigned patients with high-risk oral premalignant lesions (OPLs) to receive GTE at 500 mg/m2, 750 mg/m2, or 1000 mg/m2 or placebo TID for 12 weeks, evaluating biomarkers in baseline and 12-week biopsies. The OPL clinical response rate was higher in all GTE arms (n=28; 50%) versus placebo (n=11; 18.2%; p=0.09) but did not reach statistical significance. However, the 2 higher-dose GTE arms (58… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
188
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(197 citation statements)
references
References 44 publications
3
188
0
2
Order By: Relevance
“…The lack of uniformity of treatment choices in these studies makes it difficult to perform a meta-analysis to examine the outcome of chemopreventive agents. 3 The best outcome so far is with lycopene-a carotenoid-which has shown a significant improvement at 5-month followup (Table 4), in a study using 4 or 8 mg. 28 A recent study 37 used a green tea extract and reported a significant clinical response (59%) compared with placebo (18%). A dose-response was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of uniformity of treatment choices in these studies makes it difficult to perform a meta-analysis to examine the outcome of chemopreventive agents. 3 The best outcome so far is with lycopene-a carotenoid-which has shown a significant improvement at 5-month followup (Table 4), in a study using 4 or 8 mg. 28 A recent study 37 used a green tea extract and reported a significant clinical response (59%) compared with placebo (18%). A dose-response was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Another ingredient, catechins, may exhibit anti-tumor activity through inhibition of nitrosamine formations and decreased chromosomal damage (Kamori et al, 1993). Additional research on green tea suggests other possible mechanisms for a variety of its ingredients including caspase mediation (Oz & Ebersole, 2010), inhibition of angiogenesis (Tsao et al, 2009), and others. Evidence for green tea in prevention of bladder cancer is variable.…”
Section: Green Teamentioning
confidence: 99%
“…Since the landmark study of 13-cis-retinoic acid, published in 1986 by Hong and colleagues, which showed that high-dose 13-cis-retinoic acid works for SCCHN prevention in patients with oral leukoplakia, but tolerability was problematic and lesions recurred shortly after the drug was stopped, numerous studies have been performed (6). Included in agents studied are low-dose retinoids and caretenoids, other antioxidant vitamins, epigallocatechin gallate (EGCG) and Bowman-Birk inhibitor compound and other nutritional organic compounds, and nonsteroidal antiinflammatory drugs, such as ketorolac and celecoxib (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Unfortunately, we are not there yet. Some studies to date have shown a pharmacodynamic effect in biomarker studies (12)(13)(14)(15)38). Markers of proliferation, such as Ki-67 by immunohistochemistry, are doable and appealing as surrogate endpoints, but showing a decline in premalignant proliferation does not equal eradication of cancer risk.…”
mentioning
confidence: 99%